Performance of concrete paving materials incorporating biomass olive oil waste ash and nano-silica - Hashem Al-Mattarneh; Musab Abuaddous; Rabah Ismail; Ahmad B. Malkawi; Yaser Jaradat; Hamsa Nimer; Mohanad Khodier (AIMS Materials Science)
This study evaluates the utilization of biomass olive oil waste ash (OA) as a concrete paving material. Concrete pavement was produced by replacing a portion of Portland cement with OA at different percentages up to 15%. An additional set of concrete pavement was prepared by incorporating OA with nano-silica (NS) at various contents up to 1.5%. The optimal replacement contents of OA or OA and NS were investigated in terms of workability, compressive strength, strength development rate, and durability. The results showed that the optimal replacement level of OA content was 7.5%. The incorporation of NS with OA increased the optimal replacement level to 15%. The incorporation of NS with OA improved the strength, durability, and workability of all mixes. The utilization of OA with NS at optimal levels can produce concrete pavements. Using NS and OA, approximately 10 % cost savings could be achieved, together with a sustainable, environmentally friendly disposal method of olive oil waste.